A Fe3O4-SiO2-TiO2 core-shell nanoparticle: Preparation and photocatalytic properties. Issue 3 (4th March 2017) - Wang, Jie; Peng, Lin; Cao, Fang; Su, Bingqin; Shi, Hong
ABSTRACT: High activity and recycling efficient are exciting characteristics of photocatalysts for water treatment. In this contribution, we report the synthesis methods and photocatalytic properties of Fe3 O4 -SiO2 -TiO2 core-shell nanoparticles (FST NPs). The magnetic Fe3 O4, which is synthesized via carbon reduction, is used as core, and the SiO2 intermitted layer and TiO2 outside layer are prepared by sol-gel method. The hierarchic structure and the components of the FST NPs were demonstrated by transmission electron microscope and X-ray diffraction. The optimum ratio of alcohol, ester, and water was determined as 4.6:12.3:1 and 30.3:12.5:1 for the SiO2 and TiO2 layers, respectively. The X-ray photoelectron spectroscopy, magnetism, and photocatalytic activity of the FST NPs were tested as well. It is found that the methyl orange solution at a concentration of 10 mg/L can be decomposed completely within 240 min by the FST NPs.